2005
DOI: 10.1097/01.ico.0000154040.80442.8b
|View full text |Cite
|
Sign up to set email alerts
|

Acute Corneal Calcification Following Chemical Injury

Abstract: The insolubility, elemental composition, and ultrastructural appearance suggest that the opacity was caused by calcium phosphate deposition. The absence of phosphorus from the listed components of the fire retardant suggests that the use of phosphate-buffered irrigation fluid or the subsequent use of phosphate-buffered drops may have contributed to the deposition of this insoluble crystalline deposit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…19,23 Bernauer et al 24 reported potential adverse effects of intensified sodium hyaluronate artificial tears in patients with various ocular surface conditions. The authors describe five cases of deep corneal calcium crystal deposition, ultimately requiring keratoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…19,23 Bernauer et al 24 reported potential adverse effects of intensified sodium hyaluronate artificial tears in patients with various ocular surface conditions. The authors describe five cases of deep corneal calcium crystal deposition, ultimately requiring keratoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The buffer and other excipients of the irrigating fluid and other topical medications should not be phosphate-based, as this can lead to acute corneal calcification. 5,6 Mechanisms of ocular damage and early intervention Understanding the mechanism of alkali injury has lead to a rational approach to management. Alkaline agents damage tissues by a variety of mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of corneal calcification has been classified as metastatic or dystrophic processes, although the mechanism is still unclear (38).…”
Section: Superficial and Deep Corneal Calcificationmentioning
confidence: 99%
“…a) The superficial type appears as a band shaped keratopathy and refers to calcium deposition in the Bowman layer and superficial structures (36)(37)(38). The causes of superficial calcification of the cornea are unknown.…”
Section: Superficial and Deep Corneal Calcificationmentioning
confidence: 99%
See 1 more Smart Citation